KOMUNIKASI INTERPERSONAL GURU DAN KETERLIBATAN BELAJAR SISWA PADA MATA PELAJARAN BAHASA INGGRIS - Lasut, Elizabeth Meiske Maythy; Omega Kanaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The lack of student involvement during the learning process is thought to be related to the communication between teachers and students that is not well established. This descriptive-quantitative research aims to prove whether teacher’s interpersonal communication has a significant relationship with students’ learning engagement in English subjects. To answer the research questions, the researcher first determined the Mean Score of each variable and then used it as a basis for determining its relationship. The respondents for this study were 83 students at Airmadidi Adventist Elementary School in grade 5 who took English Subject. The results of the analysis of the data obtained show that the English teacher exhibited the good interpersonal communication (M=4.35) and students practiced active involvement in learning (M=4.22). In addition, by using Pearson Correlation Product Moment, the results showed that there was a significant relationship between teacher’s interpersonal communication and students’ learning involvement in English subjects, with the value of p=0.00<0.05. Based on the results obtained, it is recommended that teacher should be more active in carrying out interpersonal communication with students to trigger student learning involvement during English learning.